Factors influencing the incident of stunting in toddler in Tanjung Pasir Village, Tanah Java District, Simalungun District - Dongoran, Nurmiah; Wahyudi, Wahyudi; Harahap , Reni Agustina (Science Midwifery, 2024)
Stunting in toddlers is an indication of malnutrition that is chronic in nature as a result of poor conditions that last long from birth. Stunting that occurs in the first 1000 days of life (HPK) can increase mortality and impairment of body functions. This research is to determine the factors that influence the incidence of stunting among toddlers in Tanjung Pasir Village, Tanah Jawa District, Simalungun Regency. This study used a descriptive analytic design with a cross-sectional approach. The number of respondents was 97 mothers with toddlers (24-59 months) in Tanjung Pasir village, Tanah Jawa sub-district, Simalungun Regency using simple random sampling technique. The dependent variable of this study was the incidence of stunting. Independent variables consisted of technological factors, family and social support, economics and maternal education. Data were collected using data from Tanah Jawa Health Centre and questionnaires and analysed using chi-square statistical test. There is an association between technological factors (p = 0.045), family and social support factors (p = 0.048), economic factors (p = 0.034), and educational history factors (p = 0.023) with the incidence of stunting in toddlers. There is a relationship between the variable factors and the incidence of stunting, this is evidenced by the results of the chi-square test which shows that there is a relationship between the variables tested.